2021
DOI: 10.1002/er.6936
|View full text |Cite
|
Sign up to set email alerts
|

Acid‐durable, high‐performance cobalt phosphide catalysts for hydrogen evolution in proton exchange membrane water electrolysis

Abstract: The cost of platinum group metal (PGM) catalysts is one of the major obstacles in commercializing proton exchange membrane water electrolyzers (PEMWEs).The non-PGM substituents are often more financially beneficial but low in activity and durability in the acidic environment. In this study, cobalt phosphide catalysts, which are promising non-PGM alternatives for the hydrogen evolution reaction (HER) and have enhanced durability and single-cell performance, were fabricated directly on carbon paper using the pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 89 publications
(195 reference statements)
0
6
0
Order By: Relevance
“…The difference in their electronegativities contributes to the peak shift and electron transfer. In our previous work, 57 the P‐metal state was reported to be more important than the P‐O state for both the HER activity and stability of metal phosphide catalysts. The activities of NiP and NiMoP can be explained by the competing effects between the electron‐withdrawing by P from the metal and the relative amounts of the P‐metal state.…”
Section: Resultsmentioning
confidence: 93%
“…The difference in their electronegativities contributes to the peak shift and electron transfer. In our previous work, 57 the P‐metal state was reported to be more important than the P‐O state for both the HER activity and stability of metal phosphide catalysts. The activities of NiP and NiMoP can be explained by the competing effects between the electron‐withdrawing by P from the metal and the relative amounts of the P‐metal state.…”
Section: Resultsmentioning
confidence: 93%
“…On top of that, electrodeposition is also capable to control the size and distribution of the catalyst on the conductive support by adjusting the operating parameters. Yoon et al reported an acid-durable cobalt phosphide (Co-P) catalyst synthesized via pulse electrodeposition on CP, where the P content was controlled by adjusting the applied dissolution potential [128]. The acid durability of the best-performing Co-P catalyst (Co-P-0.3, synthesized using dissolution potential of −0.3 V SCE ) was evaluated in 0.5 M H 2 SO 4 through an accelerated degradation test (ADT) comprising 500 cyclic voltammetry (CV) cycles.…”
Section: Transition Metal-based Catalystsmentioning
confidence: 99%
“…266,267 Cobalt phosphide (Co x P) is a cost-effective and efficient cocatalyst alternative to noble metals. [268][269][270][271] For example, Wang et al reported a CoP-modified CdS heterostructure catalyst. Compared to pure CdS, the CdS/CoP composite shows improved hydrogen evolution activity.…”
Section: P-n Heterojunctionmentioning
confidence: 99%